Stable rings generated by their units - Huanyin Chen (International Journal of Mathematics and Mathematical Sciences)
We introduce the class of rings satisfying (m,1)-stable range and investigate equivalent characterizations of such rings. These give generalizations of the corresponding results by Badawi (1994), Ehrlich (1976), and Fisher and Snider (1976).